A conspiracy of faith [large type] - Adler-Olsen, Jussi (Adler-Olsen, Jussi. Department Q novel, 2013)
Detective Carl Mørck has received a bottle that holds an old and decayed message written in blood. It's a cry for help from two young brothers bound in a boathouse by the sea. After floating for years, the bottle sat forgotten, unopened, on a police department windowsill, before the seal was cracked and the gruesome message, written in Danish, was analyzed. Could it be real? Who are these boys, and why weren't they reported missing? Could they still be alive? Detective Mørck follows leads to a desperate woman trapped in a brutal marriage to a man who keeps her in isolation and hides deadly secrets.